Metarhizium rileyi: A potent bio control agent against noctuids infesting groundnut is a boon to the farmers of northern transitional zone of Karnataka: Metarhizium rileyi: A potent bio control agent against noctuids infesting groundnut is a boon to the farmers of northern transitional zone of Karnataka - ROHINI SUGANDI; BASAVARAJ YENAGI; P NAGARAJU; KOLLI BHARGHAVI (Journal of Oilseeds Research, 2023)
Field monitoring was done regularly during kharif (2019-2022) & rabi/summer (2019-2021) at MARS, UAS, Dharwad, Karnataka to know the natural occurrence of entomopathogenic fungi, Metarhizium rileyi in combating the later instars of Spodoptera litura, Thysanoplusia sp. and Helicoverpa armigera at vegetative (2.2%), pod formation (36%) and maturity stage (48%) resp. In the consecutive four years, natural pathogenecity rates were very high during Kharif (August and September) which coincided with high rainfall. Local field strain is extremely virulent in supressing the mixed population of different lepidopterans. So it’s an excellent, worthy environmentally safe biocide.